Analisis Kesalahan Siswa Sekolah Menengah Pertama di Kota Tasikmalaya dalam Menyelesaikan Soal Literasi Matematis pada Materi SPLDV - Mega Nur Prabawati; Siska Ryane Muslim; Muhamad Zulfikar Mansyur (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2021)
Mathematical literacy is an important ability to be mastered, but the facts on the results of the PISA survey that Indonesia participated in showed the results of the low mathematical literacy ability of Indonesian students. To overcome the low literacy skills of students, it is necessary to know what students' errors are in solving mathematical literacy problems. This study aims to analyze the errors of junior high school students in solving mathematical literacy problems. The research used descriptive qualitative research methods. This research was conducted in 2 junior high schools in Tasikmalaya City which consisted of 1 middle level school and 1 high level school. The data in this study were obtained using a mathematical literacy test instrument on the SPLDV material given to 8th grade students. Error descriptions were obtained from analyzing the results of students' work in completing 6 levels of mathematical literacy problem. From the results of the analysis obtained problems that refer to level 1, students experience errors in building mathematical models. At level 2, students are wrong in determining the right mathematical concept to look for a number pattern that matches the given problem conditions. Problems at level 3, students are less skilled in modifying mathematical equations and do not fully understand the information presented in the questions. Problems at level 4, students find it difficult to make relevant assumptions in solving problems. At level 5 and 6 problems students are still not able to interpret every detail of information correctly and the use of mathematical concepts that are less relevant to the core of the problem.Keywords: Student error, Mathematical Literacy, SPLDV